Alcune note sull’allevamento del bestiame a Milano nella seconda metà del Duecento - Paolo Grillo (Studi di Storia Medioevale e di Diplomatica: Nuova Serie, 2019)
In Milan, in the thirteenth century, livestock was a very important resource, that is little known today, because of the few sources available. The contracts of soccida written by the notary Giovannibello Bentevoglio in 1271 show that the breeding of sheep and cattle involved a lot of little entrepreneurs in the city and in the countryside. The great demand for meat and leather from the city market made this activity very profitable.